2008
DOI: 10.1111/j.1365-2621.2006.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal processing of prawn ‘kuruma’ in retortable pouches and aluminium cans

Abstract: Prawn 'kuruma' was prepared from Indian white shrimp (Fenneropenaeus indicus), packed in conventional 301 · 206 and 401 · 411 aluminium cans and in thin profile retort pouches having a three-layer configuration of 12.5 l polyester, 12.5 l aluminium foil and 85 l cast polypropylene of size 16 · 20 cm and 17 · 30 cm. The physico-chemical tests conducted on these containers showed their suitability for thermal processing. Prawn to kuruma ratio of 65:35 was maintained in all the containers and heat processed to eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 15 publications
8
28
2
2
Order By: Relevance
“…Heating lag factor (J h ) was 1.13. The observations were in accordance to the fi ndings of Mohan et al (2008) who reported that heating lag factor (J h ) of 1.44 and 1.0 for canned and pouch processed prawn kurma, respectively. Cooling lag factor (J c ) of 1.48 was observed for the product and the results are similar to that recorded by Shankar et al (2002) in sheer fi sh curry in retort pouches and Bindu et al (2004) in ready to eat mussel meat in retort pouches.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Heating lag factor (J h ) was 1.13. The observations were in accordance to the fi ndings of Mohan et al (2008) who reported that heating lag factor (J h ) of 1.44 and 1.0 for canned and pouch processed prawn kurma, respectively. Cooling lag factor (J c ) of 1.48 was observed for the product and the results are similar to that recorded by Shankar et al (2002) in sheer fi sh curry in retort pouches and Bindu et al (2004) in ready to eat mussel meat in retort pouches.…”
Section: Resultssupporting
confidence: 92%
“…The migration residues were well below the limits described for a food contact material (FDA 1983). Water vapour transmission was lower indicating suitability of thermal processing of the pouches and the fi ndings are in accordance with results described by Vijayan et al (1998) and Mohan et al (2008). They reported that the product had more shelf life with less water transmission rate.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations